Decisions at marketplace shopee on Islamic business ethic perspective: determination of online consumer reviews and rating / Rizky Fadjar Pakaya, Mardhiyah Hayati and Siska Yuli Anita - Pakaya, Rizky Fadjar; Hayati, Mardhiyah; Yuli Anita, Siska (Universiti Teknologi Mara Selangor, 2023)
This study aims to prove and analyze the effect of online customer reviews and online customer ratings on purchase decisions in online shopping at Shopee. This type of research is quantitative research, and the data collection method used is a questionnaire method. This study's population is the Bandar Lampung people who worked and bought products online at Shopee. Purposive sampling technique, with a total sample of 100. The distribution of questionnaires using google forms. The data analysis tool used is Multiple Linear Regression Analysis using the SPSS 26 program for Windows. The results of this study indicate that online customer reviews and online customer ratings have a significant positive effect on purchase decision.